Profil Obat Antihipertensi Pada Pasien Hipertensi Dengan Penyakit Ginjal Kronis - Oki Nugraha Putra; Fitri Kamilia Krismianti; Ikadona Logos Kaukaba (Journal of Pharmaceutical and Sciences, 2023)
Hypertension is one of the cardiovascular complications of chronic kidney disease (CKD). Control of blood pressure can prevent the progression of CKD and reduce the risk of cardiovascular complications. Antihypertensive drugs are required to control blood pressure. This study aimed to describe the profile of antihypertensive drug use in hypertensive patients with CKD. It was a retrospective study using medical records of hypertensive patients with CKD at Syarifah Ambami Rato Ebu Hospital, Bangkalan, from January 2019 to August 2021. This study was conducted between November 2021 and February 2022. The profile of antihypertensive drug use is shown descriptively. Forty-two hypertensive patients with CKD who met the inclusion criteria were included in this study, with more than 90% including end-stage kidney disease. Anemia is the most common complication in hypertensive patients with CKD. Loop diuretics (furosemide) and calcium channel blockers (nicardipine, amlodipine) are the most widely used antihypertensive drugs, with percentages of 28%, 25%, and 19%, respectively. The most commonly used antihypertensive combinations were furosemide + nicardipine by 46% and the combination of furosemide + candesartan + nifedipine by 43%. This study concludes that loop diuretics and calcium channel blockers are the most widely used antihypertensive drugs in hypertensive patients with CKD.